2008
DOI: 10.1152/ajpheart.00281.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection in female rats subjected to chronic volume overload: synergistic interaction of estrogen and phytoestrogens

Abstract: Intact female rats fed a high-phytoestrogen diet are protected against adverse left ventricular (LV) remodeling induced by chronic volume overload. We hypothesized that both phytoestrogens and ovarian hormones, particularly estrogen, are necessary for this dietary-induced cardioprotection. To test this hypothesis, eight groups of female rats were studied; rats were fed either a high-phytoestrogen (+phyto) or phytoestrogen-free diet. Groups included sham-operated rats, intact rats with fistula (Fist), ovariecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 53 publications
11
48
0
Order By: Relevance
“…Female TG mice show no changes when compared with female or male NTG hearts. Differences in the development of cardiac hypertrophy between sexes have been previously noted (20,32). Thus, the increase in cardiomyocyte area and left ventricular hypertrophy with no change in heart weight to body weight ratio or female cardiac enlargement demonstrates the moderate nature of this hypertrophic phenotype.…”
Section: Resultsmentioning
confidence: 69%
“…Female TG mice show no changes when compared with female or male NTG hearts. Differences in the development of cardiac hypertrophy between sexes have been previously noted (20,32). Thus, the increase in cardiomyocyte area and left ventricular hypertrophy with no change in heart weight to body weight ratio or female cardiac enlargement demonstrates the moderate nature of this hypertrophic phenotype.…”
Section: Resultsmentioning
confidence: 69%
“…Pellets were implanted subcutaneously between the shoulder blades 2 wk prior to fistula surgery. We have previously found that a dose of 0.02 mg/kg per day produces serum levels of ϳ35 pg/ml, which was comparable to the average estrogen level in intact female rats with functional ovaries (18).…”
Section: Surgical Proceduresmentioning
confidence: 61%
“…In contrast, female rats subjected to chronic volume overload develop an essentially concentric hypertrophy without the adverse features of myocardial remodeling seen in males, affording them cardioprotection from the subsequent development of heart failure (16 -19). This cardioprotection is lost in ovariectomized rats but can be largely restored by supplementary estrogen (8,16,18). Likewise, the adverse remodeling in male rats can be significantly attenuated by estrogen supplementation (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This apparent cardioprotection is lost following ovariectomy (6). Estrogen replacement delays the development of left ventricular (LV) hypertrophy and dilation, and it prevents the onset of congestive heart failure (CHF) in ovariectomized rats with volume overload (13). However, the mechanisms of estrogen's protective effects in prevention of adverse myocardial remodeling remain unclear.…”
mentioning
confidence: 99%